Anti-inflammatory activities of ethnomedicinal plants from Dayak Abai in North Kalimantan, Indonesia - SWANDARI PARAMITA; KHEMASILI KOSALA; DZULKIFLI DZULKIFLI; DEBY INDAH SAPUTRI; ENGGAR WIJAYANTI (Society for Indonesian Biodiversity, 2017)
Paramita S, Kosala K, Dzulkifli D, Saputri DI, Wijayanti E. 2017. Anti-inflammatory activities of ethnomedicinal plants from Dayak Abai in North Kalimantan, Indonesia. Biodiversitas 18: 1556-1561. Inflammation is a normal process in the human body as a response to injury from the healing process. Meanwhile, chronic inflammation will cause new health problems to patients. Antiinflammatory drugs generally used for those conditions, have several side effects to patients. The objective of this research was to find alternative anti-inflammatory drugs, especially from natural sources. Three medicinal plants recorded from Dayak Abai in North Kalimantan, Indonesia for health problems caused by the inflammation process i.e. Amomum xanthophlebium Baker, Clerodendrum buchananii (Roxb.) Walp., and Donax canniformis (G.Forst.) K.Schum. were used as material in this research. The experimental method using carrageenan-induced rat paw edema was used followed by the resulting measurement using plethysmometer. The results showed that significant differences of AUC (area under the curve) with p = 0.001 (p < 0.05) were achieved between negative control, positive control, and treatment group with plant medicinal extracts. AUC of leaves ethanol extract of C. buchananii showed the strongest antiinflammatory activities. It could be concluded that the medicinal plants recorded from ethnomedicinal data from Dayak Abai in North Kalimantan, have anti-inflammatory activities, with C. buchananii as the most potential ones which could be further developed as a new source of the anti-inflammatory drug.